Effect of iodide on transformation of phenolic compounds by nonradical activation of peroxydisulfate in the presence of carbon nanotube: Kinetics, impacting factors, and formation of iodinated aromatic products. (October 2018) - Guan, Chaoting; Jiang, Jin; Pang, Suyan; Luo, Congwei; Yang, Yi; Ma, Jun; Yu, Jing; Zhao, Xi
Abstract: Our recent study has demonstrated that iodide (I − ) can be easily and almost entirely oxidized to hypoiodous acid (HOI) but not to iodate by nonradical activation of peroxydisulfate (PDS) in the presence of a commercial carbon nanotube (CNT). In this work, the oxidation kinetics of phenolic compounds by the PDS/CNT system in the presence of I − were examined and potential formation of iodinated aromatic products was explored. Experimental results suggested that I − enhanced the transformation of six selected substituted phenols, primarily attributed to the generation of HOI that was considerably reactive toward these phenolic compounds. More significant enhancement was obtained at higher I − concentrations or lower pH values, while the change of PDS or CNT dosages exhibited a slight impact on the enhancing effect of I − . Product analyses with liquid chromatography tandem mass spectrometry clearly revealed the production of iodinated aromatic products when p-hydroxybenzoic acid (p-HBA, a model phenol) was treated by the PDS/CNT/I − system in both synthetic and real waters. Their formation pathways probably involved the substitution of HOI on aromatic ring of p-HBA, as well as the generation of iodinated p-HBA phenoxyl radicals and subsequent coupling of these radicals. Given the considerable toxicity and harmful effects of these iodinated aromatic products, particular attention should be paid when the novel PDS/CNT oxidation technology is applied for treatment of phenolic contaminants in iodide-containing waters. Graphical abstract: Image 1 Highlights: I − enhanced transformation of phenolic compounds by the nonradical PDS/CNT system. Impacts of several critical factors on I − enhancing effect were evaluated. Iodinated aromatic products of p-HBA were formed by the PDS/CNT/I − system. Formation of iodinated aromatic products was confirmed in real waters.